Endosalpingiosis in a premenarchal girl: A case report - Meriem Oumaya; Yosra Ben Ahmed; Rim Ezzine; Takwa Mili; Mariem Marzouki; Awatef Charieg; Faouzi Nouira; Said Jlidi (Elsevier, 2024)
Introduction: The diagnosis of endosalpingiosis (ES) in the pediatric population is rare. ES is typically encountered between the third and the fifth decade of life. We present a case of ES in a premenarchal girl. Case report: A 11-year-old girl presented to the emergency room with recurrent, intermittent, abdominal pain over the previous three days, accompanied by nausea and non-bilious vomiting. She had no history of fever, weight loss, jaundice, abdominal distension, urinary problems or intestinal derangements. She had not attained menarche, and there was no family history of malignancies. On the physical exam she was hemodynamically stable, and her abdomen was tender in the right iliac fossa. Baseline blood investigations were normal. Abdominal ultrasound ruled out acute appendicitis and adnexal torsion. Due to the persistence of the abdominal pain, we did a laparoscopic exploration. We found bilateral small cystic blebs on the peritoneum attached to the fallopian tubes, and no other anomalies. We resected all the cysts/blebs. She had an uneventful recovery and was pain free without medication shortly after the operation. The final pathology revealed ES with clear margins. At 24-month follow-up, the patient has attained menarche, has regular menstrual cycles and remains symptom free. Conclusions: ES can be a source of abdominal pain in premenarchal females. Our case emphasizes the need for increased awareness among healthcare providers.